2018
DOI: 10.1159/000489649
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated Analysis of MiRNA and Genes Associated with Meat Quality Reveals that Gga-MiR-140-5p Affects Intramuscular Fat Deposition in Chickens

Abstract: Background/Aims: Poultry meat quality is affected by many factors, among which intramuscular fat (IMF) is predominant. IMF content affects the tenderness, juiciness, and favor of chicken. An increasing number of studies are focusing on the functions of microRNAs (miRNAs) during the adipogenic process. However, little is known about miRNAs associated with poultry IMF deposition, especially intramuscular adipocyte differentiation. Methods: The IMF content of two physiological stages was measured, and miRNA-Seq a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 34 publications
0
57
1
Order By: Relevance
“…Oil red O staining was performed following our previously method (Zhang et al, 2018). Cells were fixed with10% PFA for 40 min, and then stained with oil red O for 20 min.…”
Section: Oil Red O and Bodipy 493/503 Stainingmentioning
confidence: 99%
“…Oil red O staining was performed following our previously method (Zhang et al, 2018). Cells were fixed with10% PFA for 40 min, and then stained with oil red O for 20 min.…”
Section: Oil Red O and Bodipy 493/503 Stainingmentioning
confidence: 99%
“…Our previous studies suggested that miRNAs could be crucial regulator in chicken adipogenesis [8,35].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing number of studies have shown that non-coding RNAs play functional roles in various normal and pathological processes, such as microRNAs (miRNAs) [7][8][9][10] and long non-coding RNAs (lncRNAs) [11][12][13]. Although miRNAs and lncRNAs have been widely studied in adipogenesis recently, the functional roles of other classes of non-coding RNAs are still poorly understood, such as circular RNAs (circRNAs).…”
Section: Introductionmentioning
confidence: 99%
“…Under deep anesthesia, the birds were euthanized by intramuscular injection of pentobarbital (Sigma, St. Louis, MO, USA) (40mg/kg). Intramuscular and abdominal preadipocytes were isolated from the breast muscle and abdominal adipose tissue of 2 weeks old-chicken following the method described by Zhang et al [8,26]. Pollution-free treatment of animal carcasses was performed after the experiment.…”
Section: Tissues and Cell Samples Collectionmentioning
confidence: 99%
“…An increasing number of studies have shown that non-coding RNAs regulates various normal and pathological processes, such as microRNAs (miRNAs) [7][8][9][10] and long non-coding RNAs (lncRNAs) [11][12][13]. Although recent studies on the role of miRNAs and lncRNAs in adipogenesis have reached a mature stage, information on the functional roles of other classes of non-coding RNAs, such as circular RNAs (circRNAs) remains scanty.…”
Section: Introductionmentioning
confidence: 99%